Effect of Inventory Management on Financial Performance - Anita Chelimo (Uganda Christian University, 2023)
The overall objective of the study was to find out the effect of inventory management and financial performance while basing on Crown Beverages Limited Nakawa. The study was guided by three objectives; to examine the effect of inventory planning on financial performance, to examine the effect of inventory documentation on financial performance and to examine the effect of inventory tracking on financial performance at Crown Beverages Limited. The population of the study was one hundred (100). A sample size of fifty (50), was derived from a finite population. Data were generated using questionnaire, oral interviews, observations, books, journals and the internet. Data were presented in tables and analyzed using simple percentages. The findings indicate that inventory management significantly affects financial performance at Crown Beverages Limited. The study found out that inventory management is essential in the operation of any business. Inventory as an asset on the balance sheet of companies has taken on increased importance because many companies are applying the strategy of reducing their investment in fixed assets. The study also recommended that organizations should train their personnel in the area of inventory management that will empower them to be in charge for the smooth running of the inventory management activities and organizations should adopt the inventory keeping method that best suits their operations. Management in manufacturing companies to always forward planning, centralize the purchase and store function, carry out stock taking exercise periodically, top management in most organizations to emphasis on the proper inventory management techniques and measuring of efficiency deviations to identify weaknesses in the process of managing inventories, managers in organizations to undertake forward production planning. Lastly, further studies are suggested on the following areas as: the effect of materials handling techniques on employees efficiency in private organizations and the relationship between labour turnover and employees’ efficiency among private organizations in Uganda.
This is a dissertation.